Development of Interactive Physics E-Module to Improve Critical Thinking Skills - Kaharuddin Arafah; Pariabti Palloan; Cynthia Cynthia (Postgraduate, University of Mataram, 2023)
This research is Research and Development (R&D). Development is carried out with reference to the ADDIE model. The ADDIE stages include the analyze, design, development, implementation, and evaluation stages. This development research aims to analyze the results of the developed interactive physics e-modules, analyze practitioners' assessment of interactive physics e-modules, analyze the use of interactive physics e-modules that have been developed in improving students' critical thinking skills. The instruments used in this study were interactive physics e-module validation sheets, practitioner assessment questionnaires (teachers/educators), and critical thinking skills test instruments. The e-module eligibility criteria are seen from the aspect of its validity. Criteria for the practicality of the physics e-module are seen from practitioners' assessment of the interactive e-module, and the criteria for the effectiveness of the interactive physics e-module are seen from the increase in the results of students' critical thinking skills after being given interactive physics e-modules. Based on the results of the analysis, it can be concluded that the interactive physics e-module which was developed based on expert judgment using the analysis of the Aiken V index is declared valid and suitable for use, then the interactive physics e-module in terms of practitioners' assessment is in the very good category, improving students' critical thinking skills after the application of the interactive physics e-module analyzed with an N-gain of 0.35 in the medium category, this means that there is an increase in students' critical thinking skills in physics